FRI0317 Reasons for hospitalisation and immunosuppressant use in adult patients with systemic lupus erythematosus admitted to a tertiary academic medical centre. (12th June 2018) - Anastasiou, C.; Dulai, O.; Baskaran, A.; Proudfoot, J.; Verhaegen, S.; Kalunian, K.
Abstract : Background: An estimated 22% to 28% of US SLE patients are hospitalised each year. 1 SLE and other connective tissue diseases have been ranked the sixth most likely conditions to result in 30 day readmission to the hospital. 2 Objectives: To determine if the number of SLE patient hospital admissions, primary reasons for hospitalisation, and mortality have changed over time. We also sought to evaluate changes in immunosuppressant use in these patients. Methods: A retrospective chart review was conducted on all adult patients with SLE admitted to the University of California San Diego Medical Centre in 2005 and 2013. Patients were identified by SLE billing code 710.0 of the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM). Results: The number of yearly SLE patient hospitalizations decreased from 178 to 86 between the two times of observation. Infection was the most common reason for hospitalisation accounting for 39.9% of hospitalizations in 2005 versus 31.4% of hospitalizations in 2013 (p=0.29). Lupus flare accounted for 9.6% of admissions in 2005 versus 8.1% of admissions in 2013 (p=0.722). SLE patient mean length of hospital stay decreased from 7.6 days to 6.4 days compared to all patient length of stay which decreased from 6 days to 5.75 days. Seven patients (3.9%) died during their hospitalisation in 2005 as opposed no inpatient deaths in 2013. Of the 261 admissions between 2010 and 2013, six admissions resulted in death (2.3%). Corticosteroid use decreased (79.8% to 61.6%, p=0.109), while hydroxychloroquine (27.0% to 59.3%, p<0.001), mycophenolate mofetil (5.6% to 13%, p=0.060), and leflunomide (0.6% to 9.3%, p=0.008) use increased over time. Conclusions: Hydroxychloroquine and leflunomide use in hospitalised patients more than doubled from 2005 to 2013 with statistical significance. Rise in mycophenolate mofetil use and drop in corticosteroid use trended toward statistical significance. Number of hospitalizations, length of stay, and mortality decreased. Infection was the primary reason for inpatient hospitalisation and there was a decrease in admission for both infections and SLE flares between the time points although this did not reach statistical significance. We hypothesise that changing medication prescribing patterns may have altered the rate of damage accrual and mortality in SLE patients, and plan to perform a national study to further evaluate SLE hospitalisation data on a larger scale. References: [1] Chakravarty EF, Bush TM, Manzi S, et al. Prevalence of adult systemic lupus erythematosus in California and Pennsylvania in 2000: estimates obtained using hospitalization data. Arthritis Rheum2007;56(6):2092–2094. [2] Elixhauser A, Steiner C. Readmissions to U.S.Hospitals by Diagnosis, 2010: Statistical Brief #153. Healthcare Cost and Utilization Project (HCUP) Statistical Briefs. Agency for Healthcare Policy and Research. URL: http://www.ncbi.nlm.nih.gov/books/NBK52651/ [Accessed May 2016]. Disclosure of Interest: None declared